Oxidation Products from the Neolignan Licarin A by Biomimetic Reactions and Assessment of in vivo Acute Toxicity - Souza, Juliana Neves de Paula e; da Silva, Rodrigo Moreira; Fortes, Simone Silveira; de Oliveira, Anderson Rodrigo Moraes; Ferreira, Leandro S.; Vessecchi, Ricardo; Lopes, Norberto Peporine; Silva, Denise Brentan (Planta Medica, 2023)
Licarin A, a dihydrobenzofuranic neolignan presents in several medicinal plants and seeds of nutmeg, exhibits strong activity against protozoans responsible for Chagas disease and leishmaniasis. From biomimetic reactions by metalloporphyrin and Jacobsen catalysts, seven products were determined: four isomeric products yielded by epoxidation from licarin A, besides a new product yielded by a vicinal diol, a benzylic aldehyde, and an unsaturated aldehyde in the structure of the licarin A. The incubation with rat and human liver microsomes partially reproduced the biomimetic reactions by the production of the same epoxidized product of m/z 343 [M + H]+. In vivo acute toxicity assays of licarin A suggested liver toxicity based on biomarker enzymatic changes. However, microscopic analysis of tissues sections did not show any tissue damage as indicative of toxicity after 14 days of exposure. New metabolic pathways of the licarin A were identified after in vitro biomimetic oxidation reaction and in vitro metabolism by rat or human liver microsomes.
Keywords: Myristica fragrans; Myristicaceae; in vitro metabolism; biomimetic reactions; metalloporphyrins; Jacobsen catalysts; acute toxicity